In-situ photocatalytic remediation of MTBE-contaminated water: effects of organics and inorganics - Lim, L.L.P; Lynch, R.J (Elsevier Ltd, 2011)
This investigation is part of a feasibility study which uses photocatalysis as a potential technology for cleaning up contaminated groundwater. It is likely that the presence of other constituents in groundwater may affect the performance of the process. Therefore, this study was conducted to investigate the effect of organic compounds and dissolved ions on the removal efficiency of a contaminant, methyl tert butyl ether (MTBE), using a reactor reported previously, Honeycomb II. Toluene, ethylbenzene and o-xylene (TEo-X), and iron, calcium, nitrate and chloride were used to represent organic and inorganic constituents, respectively, in this study. The MTBE removal efficiency decreased with increasing TEo-X concentration. The low MTBE removal efficiency at iron concentrations of 15 and 30 mg L−1 could be suppressed by the effect of chloride ion via possible mechanisms such as OH radical scavenging and/or blocking of active sites via adsorption onto the catalyst surface in acidic conditions. The MTBE removal efficiency peaked at iron concentrations of 50 mg L−1. When flowing through the reactor in a single pass, the MTBE removal efficiency of Honeycomb II increased with increasing hydraulic residence time (HRT), similar to a previous study but at lower efficiencies. When both TEo-X and dissolved ions were present, the MTBE removal efficiency remained circa 50% after 8 h operation despite the variation of TEo-X and dissolved ion concentrations. Although the catalyst was used for six experiments prior to the double pass flow experiment, about 80% MTBE removal was achieved after two passes in 48 h, in the presence of TEo-X and dissolved ions. This study demonstrated that this photocatalytic reactor can still degrade MTBE in the presence of other constituents without any process optimisation measures and reinforces its potential use for in situ groundwater remediation.